Search for the Occurrence of Clostridium difficile and Clostridium perfringens in Pigs Within Zaria and Environs, in Kaduna State, Nigeria - Maaji, E C; Kia, S N G; Bello, M (Folia Veterinaria, 2020)
Animals have been known to be the main study subjects when investigating the epidemiology of zoonotic Gram-positive Clostridium difficile and Clostridium perfringens. This cross-sectional study was aimed at determining the occurrence of C. difficile and C. perfringens in pigs as well as the associated risk factors within Zaria and environs, in Kaduna State of Nigeria. A pre-sampling survey led to the selection of Shika, Samaru and Ungwan Mangu in the pig farming communities of Zaria and environs in Kaduna North as the study sites. Rectal swabs from 132 pigs were obtained and anaerobically cultured in fluid thioglycolate and further grown on reinforced clostridia agar. The colonies obtained were sub-cultured in Clostridium difficile moxalactam norfloxacin agar and reinforced clostridia agar containing egg yolk tellurite. C. difficile was not detected. However, C. perfringens was detected at a prevalence of 16.7 % (22/132). Isolates were tested for their susceptibility to 13 antimicrobials. Only 1 isolate (4.55 %) demonstrated susceptibility to vancomycin, gentamicin, chloramphenicol and erythromycin. Of the bivariate analyses of the risk factors studied, only the type of piggery and pig management were statistically significant (P < 0.05) for C. perfringens. Therefore, it should be recognized that there is a need for pig farmers to be enlightened about this pathogen and its prevention through good management practices and hygiene.